Cross-border use of health services: An exploratory mixed-methods project at the Mexico-Guatemala border. - Ietza Bojorquez; Marcel Arévalo; Ana L Chávez; Rosa N Gómez-Osorio; César Rodríguez-Chavez; René Leyva; Rachel Gittinger; Nirma D Bustamante (PLOS Global Public Health)
Cross-border use of health services has been studied mainly as travel from high- to low- and middle-income countries ("medical tourism"). The movement between low- and middle-income countries has been less studied. The objectives were; 1) to describe the frequency, types of services used, and health needs associated with cross-border utilization of health services at the Mexico-Guatemala border; 2) to explore the drivers of cross-border use among people living in this area. We conducted a mixed-methods study. The quantitative component was a probability survey of border crossers (March to April 2023, analysis sample n = 4,733, weighted n = 74,228). The qualitative component consisted of 28 semi-structured interviews with users and providers of health services living close to the international border (May-June 2023). Descriptive results were obtained separately and triangulated. 3.8% (CI 95% 3.1,4.7) in the sample were crossing the border for the purpose of seeking health care or purchasing medicines, 7.4% (CI 95% 5.9,9.2) had crossed the border in the past year to seek care, and 21.8% (CI 95% 18.8,25.1) to purchase medicines. According to quantitative and qualitative results, those living in Mexico were more likely to cross the border to seek care than those living in Guatemala, independent of country of birth, while crossing to Mexico to buy medicine was more common than crossing to Guatemala for the same reason. Public and private services were accessed in similar proportions, the former mostly for preventive care (vaccination) and the latter for specialized care. Qualitative results showed that the main drivers of cross-border health care use were perceived quality and geographical availability. The main drivers of cross-border buying of medicines were affordability and perceived quality. The use of private services can benefit the local economy. The use of public services for preventive purposes can be an asset for health promotion.